2019
DOI: 10.1007/978-3-030-15020-4
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Cultural Perspectives on the Experience and Expression of Love

Abstract: the material is concerned, specifically the rights of translation, reprinting, reuse of illustrations, recitation, broadcasting, reproduction on microfilms or in any other physical way, and transmission or information storage and retrieval, electronic adaptation, computer software, or by similar or dissimilar methodology now known or hereafter developed. The use of general descriptive names, registered names, trademarks, service marks, etc. in this publication does not imply, even in the absence of a specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 16 publications
(19 reference statements)
0
31
0
Order By: Relevance
“…in English (Kövecses 1986), Basque (Ibarretxe-Antuñano 2008 or French, Russian, and many other languages (e .g . Karandashev 2019) . Negative ones concern worry, Despair and pain .…”
Section: Heart Metaphors Of Emotionsmentioning
confidence: 99%
“…in English (Kövecses 1986), Basque (Ibarretxe-Antuñano 2008 or French, Russian, and many other languages (e .g . Karandashev 2019) . Negative ones concern worry, Despair and pain .…”
Section: Heart Metaphors Of Emotionsmentioning
confidence: 99%
“…The concepts present in a schema are intrinsically related to culture and comprise knowledge and experience in a specific context (Rumelhart & Norman, 1985). Then, it makes sense that even though love could be considered a universal emotion and has been an adaptive mechanism essential in our evolutionary history (Buss, 2006; Kenrick, 2006), the conceptualizations of love vary according to the cultural context in which people live (see Karandashev, 2019). Indeed, studies have shown cultural differences and similarities between love prototypes (e.g., Fehr, 1994; Munck et al, 2011; Shaver et al, 2001, see Fehr, 2006).…”
Section: Implicit Theories (Laypeople) Of Love and Prototype Approachmentioning
confidence: 99%
“…However, another factor that could account for the differences is the cultural differences between Iran and Finland. Romantic love is similar cross-culturally but some differences do exist (Feybesse & Hatfield, 2019;Karandashev, 2019). For example, culture has been shown to influence self-reported importance of personality, physical appearance, propinquity, similarity, readiness, isolation, mystery, and social standing in the development of romantic love (Sprecher et al, 1994).…”
Section: Accounting For Inconsistent Findingsmentioning
confidence: 99%